Key Considerations for Advertisers Selecting Media Platforms for CTV Campaigns - Rao, Srinivasa (Journal of Global Economy, Business and Finance, 2025)
Connected TV (CTV) advertising is rapidly gaining prominence as more consumers shift from traditional TV to streaming services. Advertisers are presented with a plethora of media platforms to choose from, each offering unique features and capabilities. This paper explores the key considerations advertisers must keep in mind when selecting a media platform for their CTV campaigns, including platform reach, targeting capabilities, data integration, creative flexibility, cost, and measurement and attribution capabilities.